Hypertension risk perception among young adults in Victoria University Kampala Uganda - Grace Afam; Annet Patience Nakalega (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Globally, hypertension is becoming a more serious public health concern, with young adults also at risk. Effective intervention techniques require an understanding of young adults' perceptions of the risk factors, enablers, and barriers to adopting healthy lifestyle choices related to hypertension. This research aims to examine hypertension risk perception among young adults at Victoria University Kampala, Uganda. Methods: Data were gathered using a structured questionnaire between November 2023 and January 2024. Convenience sampling was used to gather data from young adults at Victoria University Kampala, Uganda. Leslie Kish's formula was used to establish the sample size of 126 respondents. Multiple regression analysis was performed to examine the association between independent variables (barriers, and facilitators) and the dependent variable (perception of hypertension risk). Results: The study found that perceptions of certain risk factors, such as smoking (OR = 2.418, p = 0.035), physical inactivity (OR = 1.731, p = 0.008), unhealthy diet (OR = 2.174, p = 0.048), and chronic stress (OR = 1.514, p = 0.028), significantly influenced the likelihood of adopting healthy lifestyle choices. Among the enablers, motivation (OR = 3.491, p = 0.005), availability of time (OR = 3.015, p = 0.011), financial resources (OR = 2.164, p = 0.017), and social support (OR = 2.014, p = 0.026) were strong predictors of healthy behaviour adoption. Conclusion: Programs aimed at raising awareness of hypertension risk factors and enhancing enablers such as motivation, time management, and social support are recommended to effectively promote healthy behaviours among this population.